Analysis of Opportunities and Risks in Financial Technology Innovation for Islamic Banking in Adapting to the Changing Financial Ecosystem: A Case Study - Munthe, Raja Syahrial; Anggraini, Tuti; Harahap, Muhammad ikhsan (Borong Newinera Publisher, 2024)
This study analyzes the opportunities and risks associated with financial technology (fintech) innovations in Islamic banking, with a specific focus on Bank Syariah Indonesia (BSI) North Sumatra Regional Office. The research is driven by the rapid advancements in fintech, which are reshaping the global financial ecosystem, including the Islamic banking sector. The study aims to evaluate the impact of fintech innovations on BSI's operations and explore strategies to leverage these opportunities while addressing inherent risks. A qualitative case study approach with a descriptive-analytical method was utilized, incorporating primary data from interviews and secondary data from relevant literature. The findings highlight that BSI North Sumatra Regional Office has implemented various fintech solutions that improve operational efficiency and promote financial inclusion. However, challenges persist, particularly in regulatory compliance, cybersecurity, and technological adaptation. The study concludes that a holistic and adaptive strategy is crucial for BSI to effectively integrate fintech innovations and maintain its competitiveness in a dynamic financial ecosystem.